Overlapping but Distinct Sequences Play Roles in the Insulator and Promoter Activities of the Drosophila BEAF-Dependent scs’ Insulator - Maharjan, Mukesh (Genetics, 2020)
Chromatin domain insulators are thought to help partition the genome into genetic units called topologically associating domains (TADs). In Drosophila, TADs are often separated by inter-TAD regions containing active housekeeping genes and associated insulator binding proteins. This raises the question of whether insulator binding proteins are involved primarily in chromosomal TAD architecture or gene activation, or if these two activities are linked. The Boundary Element-Associated Factor of 32 kDa (BEAF-32, or BEAF for short) is usually found in inter-TADs. BEAF was discovered based on binding to the scs’ insulator, and is important for the insulator activity of scs’ and other BEAF binding sites. There are divergent promoters in scs’ with a BEAF binding site by each. Here, we dissect the scs’ insulator to identify DNA sequences important for insulator and promoter activity, focusing on the half of scs’ with a high affinity BEAF binding site. We find that the BEAF binding site is important for both insulator and promoter activity, as is another sequence we refer to as LS4. Aside from that, different sequences play roles in insulator and promoter activity. So while there is overlap and BEAF is important for both, insulator and promoter activity can be separated.